Measurement, Testing, and Validation Techniques in Electronics Research - Chetan Pathak (AG Volumes, 2025)
This is a review of how measurement, testing and validation methods are crucial in electronics research and why it is important in providing accuracy, reliability and reproducibility of the results of the experiment. As semiconductor devices, embedded systems, and power electronics, and communication technologies are rapidly evolving, more exact evaluation techniques have become mandatory. The paper discusses major measurement methods of electrical, thermal and signal parameters; organized methods of testing of performance, reliability and compliance and validation methods of connecting theoretical models to experimental outcome. Newcomers like automated testing, AI-assisted verification, and sophisticated instrumentation are also discussed, and their increasing importance in the current electronics study is highlighted.